Characteristics Studies of Strontium Hydrogen Phosphate Crystals - SUNDARAMOORTHI, P.; KALAINATHAN, S. (Asian Journal of Chemistry, 2010)
Strontium hydrogen phosphate [SHP] crystals are found rarely in urinary tract. The crystals were grown artificially by single and double diffusion gel growth technique. The grown crystals were found to be having good single, polycrystalline, dendrite and platelets types of morphologies. The crystal cell parameters were determined by powdered XRD method. The thermal properties were studied by thermogravimetric analysis. The surface morphology and crystal defects of well-grown crystals were analyzed by SEM and Etching studies. The SHP crystal growth processes were observed in focusing laser light and sunlight to the growth column. From the results SHP crystal nucleation rates were reduced.